1998
DOI: 10.1038/bjc.1998.166
|View full text |Cite
|
Sign up to set email alerts
|

The value of serum α-N-acetylgalactosaminidase measurement for the assessment of tumour response to radio- and photodynamic therapy

Abstract: Summary Serum activity of ax-N-acetylgalactosaminidase (NaGalase), the extracellular matrix-degrading enzyme that appears to be produced exclusively by cancer cells, was measured in mice bearing SCCVII tumours (squamous cell carcinoma). The NaGalase levels in these mice increased with time of tumour growth and were directly proportional to tumour burden. After exposure of SCCVII tumours to a single X-ray dose of 20 Gy, the serum NaGalase levels gradually decreased during the first 10 days after treatment (to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 16 publications
2
20
0
1
Order By: Relevance
“…The MAF precursor activity and serum Nagalase activity have been used as diagnostic indices for a variety of cancer patients [28][29][30][31][32]37,38 and as prognostic indices during radiation therapy, 28,47,48 surgical resection of tumors 29 and GcMAF therapy of tumor bearing mice. 32,37,47 In this communication, therapeutic effect of GcMAF on 16 nonanemic breast cancer patients was studied to evaluate the efficacy of GcMAF for metastatic mammary adenocarcinoma. The prognostic significance for the MAF precursor activity and serum Nagalase activity of breast cancer patients is reported.…”
mentioning
confidence: 99%
“…The MAF precursor activity and serum Nagalase activity have been used as diagnostic indices for a variety of cancer patients [28][29][30][31][32]37,38 and as prognostic indices during radiation therapy, 28,47,48 surgical resection of tumors 29 and GcMAF therapy of tumor bearing mice. 32,37,47 In this communication, therapeutic effect of GcMAF on 16 nonanemic breast cancer patients was studied to evaluate the efficacy of GcMAF for metastatic mammary adenocarcinoma. The prognostic significance for the MAF precursor activity and serum Nagalase activity of breast cancer patients is reported.…”
mentioning
confidence: 99%
“…NaGalase is an extracellular matrix-degrading enzyme that is produced exclusively by cancer cells (Yamamoto et al, 1996). NaGalase levels in mice bearing squamous cell carcinoma increased with time of tumor growth and were directly proportional to tumor burden (Korbelik et al, 1998). Thus, in mammary cancer cells, growthsuppressive effect of glucocorticoids may be mediated through the downregulation of NaGalase, MKP-2, and IEX-1/Dif-2, while growth-promoting effect of progestins may be mediated through the induction of Mac-2 BP/90K, INHBB, and Pim-2.…”
Section: Differential Gene Regulation By Glucocorticoids and Progementioning
confidence: 89%
“…8,9 All major allelic forms of DBP can be converted to GcMAF (by the action of b-galactosidase of inflammation-activated B cells and, for Gc1 proteins, inflammation-activated T-cell sialidase [4][5][6][7] ) despite the fact that Gc2 lacks O-linked trisaccharidic glycosylation, 4,5 suggesting the presence of a low occupation, alternative glycosylation site on Gc2 proteins (which must be genetically conserved in Gc1F and Gc1S proteins). 4,5,8 Studies in cancer patients have shown that highserum levels of a-N-acetylgalactosaminidase (nagalase) activity correspond in linear fashion to both tumor burden 15,16 (in mice and humans) and, inversely, GcMAF ''precursor activity'' in humans. 2,3 This ''precursor activity'' has been assigned (without direct structural evidence) as the quantity of O-linked trisaccharide glycosylated DBP available in patient plasma, and is reported to be significantly depleted or even eliminated in cancer patients based on activity studies.…”
Section: Introductionmentioning
confidence: 99%